Study on anti-progressive collapse performance of cellular steel frames with different web opening shapes. (January 2023) - Zheng, Han; Qiao, Huiyun; Chen, Yu; Yang, Bo; Zhu, Bin; Lai, Lifang
Abstract: In this paper, cellular beam-column joints with different opening shapes were taken as the object of study to investigate the resistance to progressive collapse of weakened beam-column joints through a combination of experiments and numerical simulations. Opening shapes include circular, rectangular and hexagonal. The development laws of failure mode, vertical force–deformation response, internal force development and resistance mechanism of the specimens were analyzed, and based on the validated finite element model, the effects of weakening parameters of openings with different opening shapes on the performance of the beam-column joints against progressive collapse were studied. The results demonstrate that the load carrying capacity and deformation capacity of cellular joints with different opening shapes have different degrees of improvement compared with the foundation joints, and exhibit the largest deformation in the first opening area near the column flange, where the ductile failure at the weakened section occurs in the hexagonal cellular opening, and the catenary effect can be fully developed, showing the best performance under the designed opening size, rectangular is the second and circular the worst. In addition, the failure mode and load carrying capacity of the specimens can be effectively improved by changing the opening weakening parameters. Increasing the opening diameter (parameter a ) and opening edge distance (parameter c ) within a reasonable range can effectively improve the vertical resistance and deformability of the specimens, and the effect of opening spacing (parameter b ) on the structural load response is negligible. In the design of collapse resistance of cellular beam-column joints, it is recommended to increase the values of parameters a and c appropriately and to reduce the value of parameter b appropriately under the premise of ensuring the structural load carrying capacity, which is more conducive to the catenary action.